Numerical modelling of the dissolution of drug nanocrystals and its application to industrial product development - Bastian Bonhoeffer; Andreas Kordikowski; Edgar John; Michael Juhnke (International Association of Physical Chemists (IAPC), 2022)
The apparent solubility of drug nanocrystals in equilibrium was experimentally determined for a drug-stabilizer system with different particle size distributions. True supersaturation was identified for ultrafine drug nanocrystals with an almost 2-fold increase compared to the thermodynamic solubility of related coarse drug crystals, highlighting their enabling potential to enhance bioavailability. The experimental results were applied to investigate in silico the associated dissolution behavior in a closed system by numerical modeling according to the Ostwald-Freundlich and Noyes-Whitney / Nernst-Brunner equations. Calculated results were found to be in agreement with the experimental results only when the entire particle size distribution of drug nanocrystals was considered. In silico dissolution, studies were conducted to simulate the complex interplay between drug nanocrystals, dissolution conditions and resulting temporal progression during dissolution up to the equilibrium state. Calculations were performed for selected in vivo and in vitro scenarios considering different drug nanocrystal particle size distributions, drug amount, dissolution media and volume. The achieved results demonstrated the importance of ultrafine drug nanocrystals for potential bioavailability improvement and the functional applicability of the modeling approach to investigate their dissolution behavior for configurable formulation variables in product development in terms of in vivo and in vitro relevant conditions. ©2022 by the authors. This article is an open-access article distributed under the terms and conditions of the Creative Commons Attribution license (http://creativecommons.org/licenses/by/4.0/).